Ionizing Electrons on the Martian Nightside: Structure and Variability. Issue 5 (28th May 2018) - Lillis, Robert J.; Mitchell, David L.; Steckiewicz, Morgane; Brain, David; Xu, Shaosui; Weber, Tristan; Halekas, Jasper; Connerney, Jack; Espley, Jared; Benna, Mehdi; Elrod, Meredith; Thiemann, Edward; et al.
Abstract: The precipitation of suprathermal electrons is the dominant external source of energy deposition and ionization in the Martian nightside upper atmosphere and ionosphere. We investigate the spatial patterns and variability of ionizing electrons from 115 to 600 km altitude on the Martian nightside, using CO2 electron impact ionization frequency (EIIF) as our metric, examining more than 3 years of data collected in situ by the Mars Atmosphere and Volatile EvolutioN spacecraft. We characterize the behavior of EIIF with respect to altitude, solar zenith angle, solar wind pressure, and the geometry and strength of crustal magnetic fields. EIIF has a complex and correlated dependence on these factors, but we find that it generally increases with altitude and solar wind pressure, decreases with crustal magnetic field strength and does not depend detectably on solar zenith angle past 115°. The dependence is governed by (a) energy degradation and backscatter by collisions with atmospheric neutrals below 220 km and (b) magnetic field topology that permits or retards electron access to certain regions. This field topology is dynamic and varies with solar wind conditions, allowing greater electron access at higher altitudes where crustal fields are weaker and also for higher solar wind pressures, which result in stronger draped magnetic fields that push closed crustal magnetic field loops to lower altitudes. This multidimensional electron flux behavior can in the future be parameterized in an empirical model for use as input to global simulations of the nightside upper atmosphere, which currently do not account for this important source of energy. Key Points: We investigate the patterns and variability of electron impact ionization frequency (EIIF) below 600 km on the Martian nightside EIIF generally increases with altitude and solar wind pressure and decreases with crustal magnetic field strength Patterns of EIIF reflect the combined solar wind‐dependent topology of Mars' variable draped IMF and planet‐fixed crustal magnetic fields